Simulation of the Effect of Water Temperature on Domestic Biomass Boiler Performance - Pablo Eguía; Miguel A. Álvarez Feijoo; Roberto Comesaña; Miguel A. Gómez (Energies, 2012)
This paper presents a methodology to simulate the combustion of fixed beds of biomass particles using computational fluid dynamics (CFD) techniques. The models presented were used in the simulation of a domestic pellet boiler working under operating conditions and the model predictions were compared with measurements of heat transfer, temperature and species concentration. The same procedure was then used to simulate the same domestic boiler working with different values of water temperature and the influence of water temperature variations on the main variables was analyzed.